2012
DOI: 10.7763/ijcea.2012.v3.161
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Malaysian Leachate Sample Using Electrocoagulation

Abstract: A real leachate sample, taken from a Kuala Lumpur suburban area, was used in order to investigate the efficiency of electrocoagulation using Fe electrodes as both cathodes and anodes to reduce chemical oxygen demand (COD) and color of the sample. The effects of pH value and current density on the efficiency of the leachate treatment were investigated. Meanwhile, it was well understood that using this approach for the treatment of the studied leachate could successfully lower the COD value and color of the leac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The data used in this work were collected from several scientific articles published in the last few decades. 6,40,41,48–89 The characteristics of the leachate, the parameters reported in the treatment and the response variables were considered. Only articles related to landfill leachate treatment by EC were considered, even if EC was considered a single or a combined process.…”
Section: Methodsmentioning
confidence: 99%
“…The data used in this work were collected from several scientific articles published in the last few decades. 6,40,41,48–89 The characteristics of the leachate, the parameters reported in the treatment and the response variables were considered. Only articles related to landfill leachate treatment by EC were considered, even if EC was considered a single or a combined process.…”
Section: Methodsmentioning
confidence: 99%
“…Leachate also known having high chemical oxygen demand (COD), high levels of ammonia and phosphorus as well as total dissolved solid content (TDS) [7]. To reach environmental friendly criteria for landfill leachate, chemical pollution should be minimized to an acceptable discharge limit [8].…”
Section: -2506mentioning
confidence: 99%
“…Some study used a lot of electrodes to treat the wastewater, which cause the treatment cost to increase [6]. Then, from previous study by Li (2011), Mosoumeh (2012) and Shivayogimath (2013) showed that higher current density and duration of current flow, resulted in effectiveness EC process [7,8,9]. Besides that, coagulation-flocculation process is widely used to treat wastewater however it still has disadvantages such as producing a lot of sludge and expensive coagulant needed [10].…”
Section: Introductionmentioning
confidence: 99%